FRAUD RISK MANAGEMENT IN PUBLIC SECTOR ACCOUNTING: A BEHAVIORAL PERSPECTIVE - Kathleen Asyera Risakotta; Amiruddin Amiruddin; Rahmawati HS (CV. Adiba Aisha Amira, 2026)
This study aims to examine fraud risk management in public sector accounting using a behavioral perspective through a literature review approach. The primary focus of the study is to understand how individual and organizational behavioral factors influence the emergence of fraud risk and the effectiveness of implemented control mechanisms. The method used is a systematic literature review, reviewing various scientific sources such as international journals, academic books, and institutional reports relevant to the topic of fraud risk management and organizational behavior in the public sector. The results of the study indicate that fraud risk is influenced not only by weaknesses in the internal control system but also by behavioral aspects such as pressure, rationalization, and opportunity, as explained in the fraud triangle theory. Furthermore, organizational culture, individual integrity, and ethical leadership play a significant role in preventing and detecting fraud. The research findings also indicate that the implementation of effective fraud risk management requires a holistic approach that integrates technical and behavioral aspects, including increasing ethical awareness, training, and strengthening oversight systems. Thus, the behavioral perspective provides an important contribution to enriching fraud prevention and handling strategies in the public sector.